2018
DOI: 10.2147/ndt.s158339
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of oral olanzapine treatment transitioned from rapid-acting intramuscular olanzapine for agitation associated with schizophrenia

Abstract: ObjectiveTo assess the effectiveness and safety of oral olanzapine treatment transitioned from rapid-acting intramuscular olanzapine (RAIM) in patients with acute agitation associated with schizophrenia in a real-world clinical setting.MethodsThe postmarketing surveillance study with a 3-day observational period after the last RAIM administration was conducted (original study). Following this, an extended study was added for patients who received oral olanzapine after RAIM administration during the original st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“… 15 Olanzapine is a new type of antipsychotic drug with high affinity, which can bind with multiple receptors such as 5-hydroxytryptamine, dopamine D, α - epinephrine and histamine H. The biggest difference between olanzapine and risperidone is that olanzapine can prevent the discharge of dopaminergic neurons (midbrain limbic system), protect the striatum motor function of patients, and improve the cognitive impairment of patients. 16 From the perspective of pharmacological effect, olanzapine combined with risperidone may produce some synergistic effects similar to that of the second generation antipsychotics combined with the first generation drugs.…”
Section: Discussionmentioning
confidence: 99%
“… 15 Olanzapine is a new type of antipsychotic drug with high affinity, which can bind with multiple receptors such as 5-hydroxytryptamine, dopamine D, α - epinephrine and histamine H. The biggest difference between olanzapine and risperidone is that olanzapine can prevent the discharge of dopaminergic neurons (midbrain limbic system), protect the striatum motor function of patients, and improve the cognitive impairment of patients. 16 From the perspective of pharmacological effect, olanzapine combined with risperidone may produce some synergistic effects similar to that of the second generation antipsychotics combined with the first generation drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Olanzapine is absorbed well orally and has a bioavailability of about 85% [ 40 ]. In the treatment of agitation associated with schizophrenia, switching from intramuscular injections to oral preparations may help treat the disease in the long term and improve patients’ compliance to treatment [ 46 ]. Previous studies have shown that almost all patients who received intramuscular injections of olanzapine experienced agitation [ 47 ].…”
Section: Effects Of Olanzapine On Different Administration Routesmentioning
confidence: 99%
“…A study exploring the efficacy and safety of oral versus intramuscular olanzapine in schizophrenia indicated that intramuscular injection of 10 mg olanzapine effectively reduced acute agitation within 24 h among patients with schizophrenia. When switching from intramuscular injection to oral administration, the reduction in irritability lasted up to four days after oral administration, and patients who took olanzapine orally did not have dystonia, which could be induced by intramuscular injection [ 46 ]. As for the intravenous injection, the literature almost exclusively mentions the use of intravenous olanzapine among patients with anxiety in the emergency department [ 48 ].…”
Section: Effects Of Olanzapine On Different Administration Routesmentioning
confidence: 99%